Target detection approach for DRM-based passive bistatic radar - Zhixin Zhao (The Journal of Engineering, 2019)
This study discussed the problem of target detection for digital radio mondiale (DRM)-based passive bistatic radar (PBR). In the surveillance signal, the power of zero Doppler contribution (ZDC) is stronger than the echoes of weak targets. These targets can hardly be shown in the range-Doppler map of classical cross-ambiguity function (CAF). The clutter should be removed before using CAF-matched correlator. The authors utilised Doppler channel detector (CHAD) to solve the above problem for DRM-based PBR in this study. It can unify the ZDC rejection and the target detection in one process. Compared to CAF detector, the CHAD had a lower random pedestal for low Doppler frequency shifts. The results of experiment data proved the effectiveness of the CHAD for DRM-based PBR.